Empowerment of Health Cadres in Efforts to Prevent Cardiac Emergency in the Community - Loetfia Dwi Rahariyani; Siti Maimuna; Tanti Wulandari; Kusmini Suprihatin; Krisnawati Krisnawati (Pusat Unggulan Ipteks Poltekkes Kemenkes Surabaya, 2023)
Urban communities are prone to suffering from coronary heart disease, due to working hard and spending a lot of time outside the home. Many people die suddenly at work, while driving, exercising or staying at home; suspected of having a heart attack. The active role of the community to overcome this problem is very much needed, and community empowerment is a good strategy, especially for health cadres. In this case, it is necessary to carry out training, then identify an increase in the knowledge of health cadres about the prevention of cardiac emergencies. The results of the study show that the role of health cadres is indispensable in efforts to prevent cardiac emergencies in the community.